On BRK-Algebras - Ravi Kumar Bandaru (International Journal of Mathematics and Mathematical Sciences)
The notion of BRK-algebra is introduced which is a generalization of BCK/BCI/BCH/Q/QS/BM-algebras. The concepts of 𝐺-part, 𝑝-radical, medial of a BRK-algebra are introduced and studied their properties. We proved that the variety of all medial BRK-algebras is congruence permutable and showed that every associative BRK-algebra is a group.